Design and simulation of a high performance lateral BJTs on TFSOI - Saad, Ismail; Ismail, Razali (2006)
Lateral BJT's have received renewed interest with the advent of BiCMOS and Silicon on Insulator (SOI) technology. It's been reported in [1] that a 67 GHz fmax novel lateral BJT's on TFSOI has been fabricated with a simplified process. This paper presents an investigation of this high performance transistor by using 2D process and device numerical simulation. Accurate geometrical structure and reasonably good doping profiles with a simple fabrication process are successfully achieved in the process simulation. However, a careful attention is required to define the mesh for the device to obtain an accurate measurement of device characteristics. With a base, low-doped collector, emitter and high-doped collector concentrations of 3 times 1017 cm-3, 1.0 times 1017 cm-3, 5 times 1020 cm-3 and 3 times 1020 cm-3 respectively, a variation of 0.1-0.13 mum base width is observed. I-V and frequency performance of these transistors are simulated and analyzed. Y-parameter measurement at frequency 10 MHz - 1000 GHz shows a 21 GHz fmax was successfully achieved at VBE=0.7 V, VCE=2.0 V and ICE=6.0 muA.